Technology Landscaping in Indian Meat Sector to Meet the Future Demand and Strengthening Business : doi: 10.5958/2581-6616.2021.00008.6 - Sen, A.R.; Muthukumar, M.; Naveena, B.M.; K, Girish; Patil, S.; Banerjee, Rituparna; Reddy, G.V. Bahskar; Mandal, P.K.; M., Devakrupa (Journal of Meat Science, 2021)
The meat industry is influenced by technological developments which should be accepted by the stakeholders/consumers’ and it should be feasible as consumers’ preferences are one of the most important factors. Technology plays a crucial role across the entire lifecycle of a product, and communicating it in a translucent way is significant for building brand loyalty. Adapting to new technology can be game-changing and a thorough, in-depth view of a technology space is needed to make the right decision. Technology landscaping involves examining and outlining the landscape for technology by uncovering trends, research gaps, overlaps, and links and is also helpful for directing research and developing strategy. Technology landscape maps can help to build awareness of strategic technologies and identify opportunities at the intersection of emerging technologies and customer needs. Today with modern disruptive technologies, the food industry is booming. While the meat industry was a late adopter, companies are currently seeking to transform themselves digitally through better data collection and more control over their machinery. Technology landscaping has provided the best solutions to the existing problems in the meat sector. The recent Industry 4.0 technologies like Big Data, Artificial Intelligence, Internet of things, Blockchain Technology, and Robotics are being used in the livestock sector to enhance farm automation, clean meat production, and transparency throughout the supply chain right from the manufacturer to the end-users. Despite having these all-lucrative advantages of emerging technologies in the food sector; the adoption of technology is at a very slow pace. The main reason behind this is the higher initial investment, paucity of skilled manpower, and maintenance of relevant protocols. Another thing is majority of meat processors are small and medium-sized organizations. Technology has the potential to change the competitive landscape in the market and as technology disrupts the market there will also be discontinuation of the present market structure.